2010
DOI: 10.1097/brs.0b013e3181dcda75
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience Using Cortoss for Treating Vertebral Compression Fractures With Vertebroplasty and Kyphoplasty

Abstract: These studies indicate Cortoss is safe and effective in treating osteoporotic VCF using vertebroplasty or kyphoplasty. Pain relief and restoration of function with Cortoss is comparable to results found in the literature for polymethylmethacrylate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Additionally in the VP group the authors reported one psoas hematoma, one injury to the thecal sac (managed conservatively [21]), and one osteomyelitis requiring further surgery [22]. No cases of symptomatic cement extravasation were reported in the BKP arm, while one case of osteomyelitis was recorded [69]. The only study describing SAEs in detail was the FREE trial [8] (BKP vs. NSM randomized) where the profile was similar in both groups: 58 events in 149 cases in the BKP arm and 54/151 in the NSM arm.…”
Section: Serious Adverse Eventsmentioning
confidence: 98%
“…Additionally in the VP group the authors reported one psoas hematoma, one injury to the thecal sac (managed conservatively [21]), and one osteomyelitis requiring further surgery [22]. No cases of symptomatic cement extravasation were reported in the BKP arm, while one case of osteomyelitis was recorded [69]. The only study describing SAEs in detail was the FREE trial [8] (BKP vs. NSM randomized) where the profile was similar in both groups: 58 events in 149 cases in the BKP arm and 54/151 in the NSM arm.…”
Section: Serious Adverse Eventsmentioning
confidence: 98%
“…10 Bis-GMA composites were first used as synthetic bone void fillers in vertebral and long bone augmentation procedures and were found to be advantageous over other allografts in animal and clinical studies. [12][13][14][15] Their mechanical advantages, ease of application, and successful clinical results make them popular in operating theaters. 10,16 Biomechanical characteristics of bis-GMA-based materials in the living tissue were evaluated in only 1 animal study, which was conducted in long bones of rabbits and sheep.…”
mentioning
confidence: 99%
“…107,108 Cortoss (Orthovita) contains bioactive glass and has been successfully used in kyphoplasty and vertebroplasty as well as spinal fusion. [43][44][45] Collagen and collagen/HA. Collagen is an osteoconductive material and when used alone provides minimal structural support as a bone graft substitute, which limits its use clinically.…”
Section: Resultsmentioning
confidence: 99%